Structural and metamorphic equivalence across theLHS-HHCS contact, Sikkim Himalaya – indicator of post-deformation metamorphism or the wrong MCT? - Gupta, Saibal; Mondal, Suman (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1261 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.59